2017
DOI: 10.1038/s41598-017-05623-3
|View full text |Cite
|
Sign up to set email alerts
|

Association Of Plasma And Urinary Mutant DNA With Clinical Outcomes In Muscle Invasive Bladder Cancer

Abstract: Muscle Invasive Bladder Cancer (MIBC) has a poor prognosis. Whilst patients can achieve a 6% improvement in overall survival with Neo-Adjuvant Chemotherapy (NAC), many do not respond. Body fluid mutant DNA (mutDNA) may allow non-invasive identification of treatment failure. We collected 248 liquid biopsy samples including plasma, cell pellet (UCP) and supernatant (USN) from spun urine, from 17 patients undergoing NAC. We assessed single nucleotide variants and copy number alterations in mutDNA using Tagged-Amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 44 publications
(53 reference statements)
5
96
1
2
Order By: Relevance
“…Comparison of plasma, USN and UCP data did not reveal a clear relationship in detection amongst these compartments (Fig. 2C), confirming previous observations in bladder cancer [13,21] . Considering only those patients for which we had access to plasma and urine, the detection rate increased to 9/21 (42.9%).…”
Section: Untargeted Analysis Of Ctdna In Plasma and Urine From Patiensupporting
confidence: 89%
See 3 more Smart Citations
“…Comparison of plasma, USN and UCP data did not reveal a clear relationship in detection amongst these compartments (Fig. 2C), confirming previous observations in bladder cancer [13,21] . Considering only those patients for which we had access to plasma and urine, the detection rate increased to 9/21 (42.9%).…”
Section: Untargeted Analysis Of Ctdna In Plasma and Urine From Patiensupporting
confidence: 89%
“…As sampling of biofluids collected in close proximity to the tumour site may improve detection [13,19] , we analysed urine supernatant (USN) samples from 21 DIAMOND cohort patients. Applying tMAD to urine for the first time (Fig.…”
Section: Untargeted Analysis Of Ctdna In Plasma and Urine From Patienmentioning
confidence: 99%
See 2 more Smart Citations
“…Other workers have also utilised cpDNA and targeted deep sequencing for the identification of genomic alterations in urine samples from patients with UBC [7,9,30]; however, few studies have directly compared cpDNA and cfDNA by targeted deep sequencing in this setting [11,31]. Although cpDNA is conventionally utilised for urinary biomarker studies (principally due to higher yields than cfDNA), we have shown that SM detection in urinary cfDNA works as well as (or marginally better than) SM detection in cpDNA.…”
Section: -Gene Panel For Urinary Ubc Diagnosismentioning
confidence: 77%